Nationality and Statelessness: Handbook for Parliamentarians N° 22 - Marilyn Achiron (2010)
This handbook aims to provide parliamentarians with a broad description of the international principles regulating nationality and statelessness. States hold a broad discretion with which to define their initial body of citizens and the conditions for acquiring, losing, and retaining citizenship. However, human rights principles developed throughout the 20th century limit this discretion if it results in statelessness and/or if it is applied in a discriminatory manner.